Perioperative and Long-Term Outcomes of Robot-Assisted Partial Nephrectomy: A Systematic Review. Issue 1 (January 2021) - Tang, Amber B.; Lamaina, Margherita; Childers, Christopher P.; Mak, Selene S.; Ruan, Qiao; Begashaw, Meron M.; Bergman, Jonathan; Booth, Marika S.; Shekelle, Paul G.; Wilson, Mark; Gunnar, William; Maggard-Gibbons, Melinda; et al.
Background: Adoption of the robotic surgical platform for small renal cancers has rapidly expanded, but its utility compared to other approaches has not been established. The objective of this review is to assess perioperative and long-term oncologic and functional outcomes of robot-assisted partial nephrectomy (RAPN) compared to laparoscopic partial nephrectomy (LPN) and open partial nephrectomy (OPN). Methods: A search in PubMed, Embase, and Cochrane (2010-2019) was conducted. Of 3877 articles screened, 7 observational studies were included. Results: RAPN was associated with 24-50 mL less intraoperative blood loss compared to LPN and 39-84 mL less than OPN. RAPN also demonstrated trends of other postoperative benefits, such as shorter length of stay and fewer major complications. Several studies reported better long-term functional kidney outcomes, but these findings were inconsistent. Recurrence and cancer-specific survival (CSS) were similar across groups. While RAPN had a 5-year CSS of 90.1%-97.9%, LPN and OPN had survival rates of 85.9%-86.9% and 88.5-96.3% respectively. Conclusions: RAPN may be associated with a lower estimated blood loss and comparable long-term outcomes when compared to other surgical approaches. However, additional randomized or propensity matched studies are warranted to fully assess long-term functional kidney and oncologic outcomes.